THE INFLUENCE OF POS AND FRINGE BENEFITS ON EMPLOYEE PERFORMANCE WITH OCB MEDIATING VARIABLE - Cindy Pramita; Budi Eko Soetjipto; Sopiah Sopiah (SEAN Institute, 2023)
Job resources provide close attention to employees to POS in the workplace, provide rewards in the form of fringe benefits, and provide feedback on employee behavior and OCB. it acts as a driving force to achieve performance goals. Companies implementing OCB may face challenges due to a lack of understanding about OCB. POS is necessary to build bridges between managers and employees, especially in human resource development (HRD). The importance of HRD when evaluating employee performance their future goals. This type of research is descriptive and explanatory research using a quantitative approach. This research is used to explain problems related to POS, Fringe Benefits, Employee Performance, and OCB. In this research design, the analysis used is SEM-PLS analysis. The population of this research is finite, where the population studied is known, namely all employees of PT KAI Balai Yasa Surabaya using a non-probability sample technique of 159 respondents. The results of this research show that there is a positive and significant influence between POS directly on employee performance, there is no positive or negative influence and there is no direct influence between fringe benefits on employee performance, there is a positive and significant influence between OCB directly on employee performance, positive influence and positive and significant direct influence of POS on OCB, positive and significant direct influence of fringe benefits on OCB, positive and significant direct influence of POS on employee performance mediated by OCB, positive and significant direct influence of fringe benefits on employee performance mediated by OCB.